Impactos do tratamento fotocatalítico (TiO2/UV) em reservatório eutrofizado do semiárido em escala de mesocosmo. - Almeida, Antonia Samylla Oliveira (2021)
Currently, surface water resources have been affected by impacts that compromise their quantity and quality. Among the environmental problems related to this situation of degradation, there is the anthropic eutrophication, which has often promoted ideal conditions for cyanobacterial flowering events. These blooms have been a challenge in terms of water use and have led water resource management and sanitation companies to seek different technologies to carry out treatment and achieve drinking standards. It is known that these organisms present biological risks related to the production of several toxins which can cause damage to human health and to the various components of the aquatic ecosystem within the food chain. Thus, the present work aims to present a study on the impacts of treatments on eutrophic natural waters. Among these, the chemical impacts of in situ treatment using heterogeneous photocatalysis (TiO2/UV) on organisms, whose objective is to help improve water quality. To evaluate the chemical impacts, control and treatment mesocosm systems were used (containing photocatalytic reactors) fed with raw water installed in an eutrophic reservoir. Among the results, it can be seen that the action of the photocatalytic treatment (TiO2/UV) promoted an improvement in water quality and that the physical and chemical parameters turbidity, apparent color, dissolved oxygen, dissolved organic carbon and total organic carbon were significantly changed. At 72 and 168 hours the turbidity and dissolved oxygen parameters showed a reduction greater than 50% and the transparency parameter an increase greater than 50%. Additionally, it was observed that heterogeneous photocatalysis acts selectively on genera of cyanobacteria and algae, changing the diversity indices, in addition to promoting cell lysis of cyanobacteria and algae species, increasing the possibility of exposing secondary metabolites in the medium. Cyanobacteria species evaluated in the study, Planktothrix agardhii was more resistant compared to the group of phytoplanktonic organisms that showed greater resistance to treatment (algae).